Improving vasculoprotective effects of MSCs in coronary microvessels – benefits of 3D culture, sub-populations and heparin - Bumroongthai, Kobkaew; Kavanagh, Dean P. J.; Genever, Paul; Kalia, Neena (Frontiers in Immunology, 2023)
Introduction Opening occluded coronary arteries in patients with myocardial infarction (MI) damages the delicate coronary microvessels through a process called myocardial ischaemia-reperfusion injury. Although mesenchymal stromal cells (MSCs) have the potential to limit this injury, clinical success remains limited. This may be due to (i) poor MSC homing to the heart (ii) infused MSCs, even if derived from the same site, being a heterogeneous population with varying therapeutic efficacy and (iii) conventional 2D culture of MSCs decreasing their homing and beneficial properties. This study investigated whether 3D culture of two distinctly different bone marrow (BM)-derived MSC sub-populations could improve their homing and coronary vasculoprotective efficacy. Methods Intravital imaging of the anaesthetised mouse beating heart was used to investigate the trafficking and microvascular protective effects of two clonally-derived BM-derived MSC lines, namely CD317neg MSCs-Y201 and CD317pos MSCs-Y202, cultured using conventional monolayer and 3D hanging drop methods. Results 3D culture consistently improved the adhesive behaviour of MSCs-Y201 to various substrates in vitro. However, it was their differential ability to reduce neutrophil events within the coronary capillaries and improve ventricular perfusion in vivo that was most remarkable. Moreover, dual therapy combined with heparin further improved the vasculoprotection afforded by 3D cultured MSCs-Y201 by also modifying platelet as well as neutrophil recruitment, which subsequently led to the greatest salvage of viable myocardium. Therapeutic benefit could mechanistically be explained by reductions in coronary endothelial oxidative stress and intercellular adhesion molecule-1 (ICAM-1)/vascular cell adhesion molecule-1 (VCAM-1) expression. However, since this was noted by both 2D and 3D cultured MSCs-Y201, therapeutic benefit is likely explained by the fact that 3D cultured MSCs-Y201 were the most potent sub-population at reducing serum levels of several pro-inflammatory cytokines. Conclusion This novel study highlights the importance of not only 3D culture, but also of a specific CD317neg MSC sub-population, as being critical to realising their full coronary vasculoprotective potential in the injured heart. Since the smallest coronary blood vessels are increasingly recognised as a primary target of reperfusion injury, therapeutic interventions must be able to protect these delicate structures from inflammatory cells and maintain perfusion in the heart. We propose that relatively feasible technical modifications in a specific BM-derived MSC sub-population could achieve this.